U.S. Immigration Reform and the Dynamics of Mexican Migration - Khulan Altangerel; Jan C. van Ours (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2017)
The 1986 US Immigration Reform and Control Act (IRCA) was directed at tackling the problem of growing unauthorized migration through legalization of unauthorized immigrants, increasing border security and sanctioning employers who hired unauthorized immigrants. Our paper investigates how the IRCA affected the migration dynamics of Mexican immigrants focusing on their age of onset of migration and the duration of their first trip. We find that the IRCA had a positive effect in reducing unauthorized migration to the US. Although primarily aiming at unauthorized immigration, the IRCA had substantial effects on legal migration through its legalization program.
Keywords: J61; J68; 330; Immigration policy; migrant behavior